2018
DOI: 10.3390/ijerph15102247
|View full text |Cite
|
Sign up to set email alerts
|

Local Retail Food Environment and Consumption of Fruit and Vegetable among Adults in Hong Kong

Abstract: Outside of western countries, the study of the local food environment and evidence for its association with dietary behavior is limited. The aim of this paper was to examine the association between the local retail food environment and consumption of fruit and vegetables (FV) among adults in Hong Kong. Local retail food environment was measured by density of different types of retail food outlets (grocery stores, convenience stores, and fast food restaurants) within a 1000 m Euclidean buffer around individual’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
2
26
0
1
Order By: Relevance
“…In studies measuring F&V accessibility ( Table 4 ) by geographical distance between residency and RFE, the majority (n = 15) reported no influence or a negative association of distance with F&V consumption or purchasing; ; ; ( Aggarwal et al, 2014 , Caspi et al, 2012a , Curl et al, 2013 , Drisdelle et al, 2020 , Hattori et al, 2013 , Hawkesworth et al, 2017 , Jack et al, 2013 , Liese et al, 2013 , Mason et al, 2013 , Mejia et al, 2015 , Murphy et al, 2017 , Ollberding et al, 2012 , Reitzel et al, 2016 , Thornton et al, 2013 , Yamaguchi et al, 2019 ). 7 studies reported a positive association between shorter distance or increased density/convenience to food stores and higher F&V consumption when measured using a geographical information system (GIS) tool ( Clary et al, 2016 ; Curioni et al, 2020 ; Duran et al, 2016 ; McGuirt et al, 2018 ; Pessoa et al, 2015 ; Thornton et al, 2012 ; Zhang and Huang, 2018 ) and 1 Australian study identified a positive association of food store density with vegetable consumption only ( Thornton et al, 2013 ). A study conducting field audits of healthy food outlets found that neighbourhoods with more healthy food outlets had a 26% lower odds of healthier food purchasing ( Mason et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In studies measuring F&V accessibility ( Table 4 ) by geographical distance between residency and RFE, the majority (n = 15) reported no influence or a negative association of distance with F&V consumption or purchasing; ; ; ( Aggarwal et al, 2014 , Caspi et al, 2012a , Curl et al, 2013 , Drisdelle et al, 2020 , Hattori et al, 2013 , Hawkesworth et al, 2017 , Jack et al, 2013 , Liese et al, 2013 , Mason et al, 2013 , Mejia et al, 2015 , Murphy et al, 2017 , Ollberding et al, 2012 , Reitzel et al, 2016 , Thornton et al, 2013 , Yamaguchi et al, 2019 ). 7 studies reported a positive association between shorter distance or increased density/convenience to food stores and higher F&V consumption when measured using a geographical information system (GIS) tool ( Clary et al, 2016 ; Curioni et al, 2020 ; Duran et al, 2016 ; McGuirt et al, 2018 ; Pessoa et al, 2015 ; Thornton et al, 2012 ; Zhang and Huang, 2018 ) and 1 Australian study identified a positive association of food store density with vegetable consumption only ( Thornton et al, 2013 ). A study conducting field audits of healthy food outlets found that neighbourhoods with more healthy food outlets had a 26% lower odds of healthier food purchasing ( Mason et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that among young people, those who frequently shop at convenience stores have a low-quality diet (Rummo et al, 2015). The density ratio of convenience stores and fast-food restaurants versus grocery stores was also associated with decreased fruit and vegetable intake (Zhang and Huang, 2018). Recently, however, fresh fruit and vegetables have become available even at convenience stores in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnic origin of the investigated subjects is the same. However, they have apparently different living environment and lifestyles [19][20][21][22][23][24][25]. It seems likely that the differences observed are caused by lifestyle and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the GZ residents adopted a typical Chinese lifestyle, whereas most of the HK resident have a mixed westernised and Chinese lifestyle. Studies have shown that the lifestyles of HK resident are "less-healthy" including reduced physical activities, more fatty diet, staying up late and generally more stressed [19,20]. Moreover, the living environment in HK are also different from GZ.…”
Section: Introductionmentioning
confidence: 99%